Potências do seno: do produto de wallis ao comprimento da elipse - Pedrosa, Anderson Douglas Freitas (2018)
Currently in Brazil students learn the concepts of Differential and Integral Calculus for the first time in higher education, and often finish the course without knowing the motivations that gave rise to what is studied in Calculus. Scholars argue that it is possible to teach the fundamentals of Calculus already in school, based on a less rigorous and more intuitive proposal in relation to the concepts discussed. In this context, we aim to provide a perspective of thinking about Mathematics by analyzing the process of creation of John Wallis in his book "Arithmetica infinitorum", in addition to providing, in present language, a proof for the infinite product of Wallis and for the length of the ellipse. For this, the methodology used was a bibliographic research. Through this work it can be concluded that the evolution of Calculus depended on mathematicians from ancient times and that concepts that were once rudimentary became accepted by rigor with logical rigor.